1999
DOI: 10.1007/s11746-999-0008-4
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization and pressure filtration of anhydrous milk fat: Mixing effects

Abstract: Melt crystallization of anhydrous milk fat and subsequent filtration of the slurry is a common process for obtaining milk fat fractions with different physical and chemical properties. The crystallization mechanism is very complex and little is known about how the crystallizer conditions and the crystal size distribution (CSD) affect the filtration process. The objective of this study was to characterize the fractionation process and determine which geometric parameters of the crystallizer affect the filtratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
12
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 14 publications
(24 reference statements)
0
12
1
Order By: Relevance
“…Milk fat can form compound or mixed crystals (cocrystallization) during crystallization/fractionation, as discussed in previous publications (Breitschuh & Windhab, 1996;Marangoni & Lencki, 1998). Of particular interest are the studies carried out under shear (Breitschuh & Windhab, 1998;Grall & Hartel, 1992;Herrera & Hartel, 2000a;Mazzanti et al, 2003;Patience, Hartel, & Illingworth, 1999;Van Aken & Visser, 2000;Vanhoutte, Dewettinck, Vanlerberghe, & Huyghebaert, 2002), of which only our preliminary work (Mazzanti et al, 2003) followed the crystalline structure in situ. Herrera et al (Herrera & Hartel, 2000a, 2000b, 2000c showed that blends of HMF in LMF mixed at high shear lead to the formation of smaller crystals, as did faster cooling rates (Herrera & Hartel, 2000a, 2000bHerrera & Hartel, 2000c).…”
Section: Introductionmentioning
confidence: 91%
“…Milk fat can form compound or mixed crystals (cocrystallization) during crystallization/fractionation, as discussed in previous publications (Breitschuh & Windhab, 1996;Marangoni & Lencki, 1998). Of particular interest are the studies carried out under shear (Breitschuh & Windhab, 1998;Grall & Hartel, 1992;Herrera & Hartel, 2000a;Mazzanti et al, 2003;Patience, Hartel, & Illingworth, 1999;Van Aken & Visser, 2000;Vanhoutte, Dewettinck, Vanlerberghe, & Huyghebaert, 2002), of which only our preliminary work (Mazzanti et al, 2003) followed the crystalline structure in situ. Herrera et al (Herrera & Hartel, 2000a, 2000b, 2000c showed that blends of HMF in LMF mixed at high shear lead to the formation of smaller crystals, as did faster cooling rates (Herrera & Hartel, 2000a, 2000bHerrera & Hartel, 2000c).…”
Section: Introductionmentioning
confidence: 91%
“…Among the key aspects in particle characterisation during crystallisation are crystal size distribution (CSD) and crystal population. It has been shown that the separation efficiency of crystals during the filtration process is largely determined by the CSD and this in turn directly affects the quality and quantity of the resultant filtration products [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Samples crystallized at the highest shear rates produced the smallest crystals and the narrowest particle size distribution (6,7). At low agitation, agglomeration took place, whereas at high shear rates, smaller crystals were formed because of an enhanced nucleation rate (6,8) and breakdown of crystals by the shear forces of the impeller (5,9). Grall and Hartel (8) found the same effect at 30 and 20°C but the opposite at 15°C.…”
mentioning
confidence: 99%
“…Deffense (4) discussed four factors that influence crystallization of milk fat during fractionation: oil composition, polymorphism, rate of cooling, and intersolubility. In addition, the technique used to crystallize milk fat (type of crystallizer, impeller, and operating conditions) can significantly affect the process (5). Several process parameters will be discussed in more detail.…”
mentioning
confidence: 99%
See 1 more Smart Citation